f(x)=e^(sinx) ,则f'(x)=
A: e^(sinx)
B: e^(cosx)
C: (e^(sinx))cosx
D: e^(-cosx)
A: e^(sinx)
B: e^(cosx)
C: (e^(sinx))cosx
D: e^(-cosx)
C
举一反三
- 设f(x)=cosx,则f///(x) 等于 A: sinx B: cosx C: -sinx D: -cosx
- 设函数f(x)= cosx,则f ’’(x)=( ). A: sinx B: -sinx C: cosx D: -cosx
- 7. 若sinx是f(x)的一个原函数,则f’(x)=( )。 A: -sinx B: -cosx C: sinx D: cosx
- 【单选题】f(x)的导数是sinx,则f(x)的原函数为 A. sinx B. -sinx C. cosx D. -cosx
- 若f(x)dx=F(x)+C,则sinf(cosx)dx等于() A: F(sinx)+C B: -F(sinx)+C C: F(cosx)+C D: -F(cosx)+C
内容
- 0
设f(x)可导,且y=f(cosx),则dy/dx等于( )。 A: -f'(cosx)sinx B: cosx.f'(cosx) C: f'(cosx) D: f'(x)cosx
- 1
设f(x)满足f(-sinx)+3f(sinx)=4sinx•cosx(|x|≤π2).
- 2
f(x)=(cosx)^4-2sinxcosx-(sinx)^4
- 3
设f(x)是cosx的原函数,则f(x)=() A: sinx B: sinx+C C: -sinx D: -sinx+C
- 4
设f′(cosx)=sinx,则f(cosx)等于()